Fall-related experiences of stroke survivors: a meta-ethnography. Issue 7 (27th March 2017) - Walsh, Mary; Galvin, Rose; Horgan, N. Frances
Abstract: Purpose: Health professionals view falls after stroke as common adverse events with both physical and psychological consequences. Stroke survivors' experiences are less well understood. The aim of this systematic review was to explore the perception of falls-risk within the stroke recovery experience from the perspective of people with stroke.Methods: A systematic literature search was conducted. Papers that used qualitative methods to explore the experiences of individuals with stroke around falls, falls-risk and fear of falling were included. Two reviewers independently assessed the methodological quality of papers. Meta-ethnography was conducted. Concepts from each study were translated into each other to form theories that were combined through a "lines-of-argument" synthesis.Results: Four themes emerged from the six included qualitative studies: (i) Fall circumstances, (ii) perception of fall consequences, (iii) barriers to community participation and (iv) coping strategies. The synthesis revealed that stroke survivors' perceived consequences of falls exist on a continuum. Cognitive and emotional adjustment may be required in the successful adoption of coping strategies to overcome fall-related barriers to participation.Conclusions: Stroke survivors' fall-related experiences appear to exist within the context of activity and community participation. Further research is warranted due to the small number of substantive studies available for synthesis. Implications for Rehabilitation: Health care professionals should recognize that cognitive and emotional adjustment may berequired for stroke survivors to accept strategies for overcoming falls-risk, including dependenceon carers and assistive devices. Several factors in addition to physical interventions may be needed to minimize falls-risk whileincreasing activity participation. These factors could include increasing public awareness about the effects of stroke and falls-risk, and ensuring access to psychological services for stroke survivors. Rehabilitation professionals should reflect on whether they perceive there to be an appropriatelevel of fear of falling post-stroke. They should understand that stroke survivors might not conceptualize falls-risk in this way.